2007
DOI: 10.1080/02844310701552001
|View full text |Cite
|
Sign up to set email alerts
|

Local tissue reactions after nerve repair with ethyl-cyanoacrylate compared with epineural sutures

Abstract: Anastomosis of a nerve with cyanoacrylate following a lesion has previously been shown to indicate morphological and functional recovery to an extent comparable to that of conventional epineural sutures. In this study we examined the local tissue reactions after transection and repair of rat sciatic nerve, and compared sutures with a synthetic ethyl-cyanoacrylate adhesive. Many ED-1-immunoreactive macrophages were found accumulating on either side of the repair site whereas neurofilament labelling was less pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…Proximal to the seam, no evident differences between the two repair methods with respect to the number or distribution of neurofilaments could be seen. These findings, in combination with observations of nerve regeneration, starting in the proximal stump, with path-finding axons beginning to penetrate the ECA barrier, indicated that no acute axonal degeneration caused by the adhesive had taken place proximal to the seam 17 . In a parallel study, the authors demonstrated an improved motor, and a comparable sensory, recovery after experimental repair of a transected peripheral nerve with synthetic adhesive in comparison with microsutures 16 .…”
Section: Discussionmentioning
confidence: 57%
“…Proximal to the seam, no evident differences between the two repair methods with respect to the number or distribution of neurofilaments could be seen. These findings, in combination with observations of nerve regeneration, starting in the proximal stump, with path-finding axons beginning to penetrate the ECA barrier, indicated that no acute axonal degeneration caused by the adhesive had taken place proximal to the seam 17 . In a parallel study, the authors demonstrated an improved motor, and a comparable sensory, recovery after experimental repair of a transected peripheral nerve with synthetic adhesive in comparison with microsutures 16 .…”
Section: Discussionmentioning
confidence: 57%
“…A number of rat studies compared cyanoacrylate against the direct suture method on sciatic nerves and found no difference with regard to regeneration or functional outcome; however, the cyanoacrylate was simpler, although more time consuming (glue setting) [12,31,32]. A concern that has been frequently reported is the compression of regenerating nerve fibres when cyanoacrylate sets [32], along with its limited flexibility. However, this can be avoided, by overlapping the adjacent epineural sheaths and using minimal amounts of glue (Fig.…”
Section: Gluesmentioning
confidence: 95%
“…Cyanoacrylates are especially attractive due to their mechanical strength and fast cure times 5. While some studies have investigated the chronic tissue reaction and bonding of cyanoacrylates,4, 6 the short‐term consequences of cyanoacrylates on nerve tissue have not been thoroughly evaluated. Therefore, the present study attempts to address the acute effects of ethyl‐ cyanoacrylate (CA) on the functional and structural properties of repaired nerves.…”
Section: Introductionmentioning
confidence: 99%